Perspectivas del cultivo de la yuca en Colombia - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1979)
The purpose of this symposium was to prepare recommendations for the Colombian Government so that they can follow a definite course of action with regard to the planning of cassava cultivation and to ensure that the technology being generated by the research institutions is transferred to the farmer for the economic welare of the country. The conclusions reached by the 2 work groups on production and industrialization are given. (CIAT)